Planejamento da produção e da logística para empresas produtoras de sementes de milho - Junqueira, Rogério de Ávila Ribeiro (2006)
The production of corn seeds involves a complex agro-industrial production chain whose main agents must offer products of high quality and low price to stay competitive. Efficient tools to coordinate this chain are thus essential to fulfill these conditions. This work proposes a linear programming model for the strategic planning of production, storing and transportation, designed to minimize production, transportation and tax costs. The model is a function of crop planning, capacity and client demand restrictions. Although relevant to the product s final cost, taxes are not traditionally considered by the planning methods currently used by the seed industry. The raw material is generally sent to the industrial unit closest to the farm; proximity to the end consumer is of secondary importance. The main productive processes and features of the seed industry described here are based on literature and visits to plants that produce corn seeds. The mathematical model detailed in this work is implemented using the GAMS programming language and the resulting system of equations solved with CPLEX. The model was validated by using different scenarios with real-world data collected during the visits to the plants; the results were consistent with those expected. Next, the results given by the model of a case study with data for an entire season were compared against those obtained by one of the companies employing the traditional method of shortest distance between farm and industrial unit. The proposed model showed a substantial decrease in total cost when compared to the traditional method. This study also confirmed the importance of integrating taxes with production and transportation planning at the logistics level.